Epistemologi Islam: Kedudukan Wahyu sebagai Sumber Ilmu - Anwar Mujahidin (Universitas Islam Negeri Mataram, 2013)
Modern science dominated by idealism, rationalism, and empiricism has brought an acute humanity crisis. At the epistemology level, religion provides knowledge which guarantees human values, beyond ration and empirical findings. This paper aims at exploring texts of al-Qur’an as a source of knowledge. The methodology construction starts from seeing it as a paradigm-placing the holy text as an open corpus critically analyzed from linguistics, literary, and historical points of views.